Energy properties of bamboo biomass and mate co-products - Fernando Rusch; Raul de Abreu Neto; Danielle de Moraes Lúcio; Éverton Hillig (SN Applied Sciences, 2021)
Abstract Fossil fuels are being replaced by clean energy sources. Lignocellulosic biomass is considered an eco-friendly alternative, as it is a renewable raw material with high energy potential. In this context, the aim of this study was to determine the biomass energy properties of three bamboo species and mate. Thus, three species of bamboo (Bambusa vulgaris Var. Vittata, Dendrocalamus asper and Phyllostachys aurea) and Ilex paraguariensis co-products (branches and sticks) were performed. The particle size, basic density, moisture content volatiles content, ashes content, fix carbon, gross and net calorific value and energy density of these biomasses were evaluated. The biomasses analyzed here were considered suitable for energy purposes, in general, these presented volatile content between 75 and 85 %, fixed carbon content between 15 and 25% and ash content close to 1%. Average fix carbon content of all analyzed biomass was 16.13%. Ash content of Phyllostachys aurea, branches of Ilex paraguariensis and Dendrocalamus asper presented lower values, average of 1.63%. Bambusa vulgaris and Ilex paraguariensis sticks presented higher values, average of 2.65%. Phyllostachys aurea presented gross calorific value higher than, average of 19.35 MJ kg− 1. Bambusa vulgaris, Dendrocalamus asper, Ilex paraguariensis branches and sticks presented statistically equal values. Bambusa vulgaris, Dendrocalamus asper, Phyllostachys aurea showed net calorific value higher to the other analyzed materials and did not present statistical difference. Basic energy density of Phyllostachys aurea was higher to bamboo species. Ilex paraguariensis showed the lowest values with no statistical difference for branches and sticks. Article highlights Knowledge of biomass properties enables the use of residues in bioenergy production as an eco-friendly alternative. Bamboo and Mate co-products have desirable characteristics and potential to produce bioenergy. The energetic performance of bamboo biomass was superior when compared to the branches and sticks of Ilex paraguariensis.